Central Venous Catheter-Associated Blood Stream Infections Occurring in Canadian Intensive Care Units: A Six-Month Cohort Study - Donna Holton; Shirley Paton; John Conly; Joanne Embree; Geoffrey Taylor; William Thompson; Canadian Nosocomial Infection Surveillance Program (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVE: To determine the rate and risk factors associated with central venous catheter (CVC)-associated bloodstream infections (BSIs) in Canadian intensive care units (ICUs).